A personal leadership statement (2021)
This article aims to show the importance of teacher leadership, its concept, and the characteristics of a leader. In addition to defining teacher's empowerment, describing leadership empowerment, and its benefits for people around, with the purpose to encourage teachers to be good leaders and be empowered to develop classes in a better way. Likewise, this article contains personal assumptions, implications for the future, experience throughout the course, and the personal goals and expectations of the authors as future teachers, and thus be able to have adequate management in the classroom and develop the classes effectively.